Differences in throwing capacity between senior and U-18 men's team handball - Rivilla-Garcia, J.; Navarro, F.; Grande, I.; Ignatova, A. S.; Sampedro, J. (Serbian Journal of Sports Sciences, 2010)
The purpose of this investigation was to analyze the differences in general and specific throwing capacity of handball players as a function of the age category. Differences between throwing velocity to goal without and with opposition have also been addressed. Ninety four handball senior and U-18 players were assessed in four different situations of throwing: 1) heavy medicine ball throw, 2) light medicine ball throw, 3) throwing velocity without opposition and 4) throwing velocity with opposition. Senior players were found to perform far better than the U-18 players in all four throwing situations (p<0.001; t1=6.958; t2=8.244; t3=8.059; t4=5.399; df=92).Throwing velocity was higher without than with opposition for both groups; the throwing velocity of the senior group was 7.79% lower (p<0.01; t=8.317; df=47) when there was opposition, whereas U-18 players` velocity lowered by 6.03% (p<0.01; t=4.469; df=45). The results suggest that age can be a determining factor in handball players` throwing capacity, both general and specific. Likewise, the presence and interference of a goalkeeper appears to affect throwing velocity in a negative way, especially in senior players.